Implementasi Sistem Bagi Hasil Tabungan Rencana Melalui Akad Mudharabah Muthlaqah - Maurizka, Btari Salma; Sutarti, Sutarti; Rosita, Siti Ita; Taqyudin, Yudin (Jurnal Aplikasi Bisnis Kesatuan, 2024)
ABSTRACT Research through internships at Bank Syariah Indonesia Sub-Branch Office of Tanah Sareal aims to find out whether the opening procedure, product offering strategy, application of the profit sharing system of savings plans using the mudharabah muthlaqah contract has run well. Also, if there are any obstacles, what are the evaluations carried out by the bank in resolving these obstacles. The evaluation results of this study show that the procedure for opening a plan savings account and the strategy of offering plan savings products have been carried out well but need to be improved again in order to attract more customers for plan savings products. Furthermore, the profit sharing system of savings plans using the mudharabah muthlaqah contract has been implemented in accordance with the Statement of Sharia Financial Accounting Standards (PSAK) Number 105 concerning mudharabah accounting, where customers will receive a ratio for each month. The bank will always inform the customer if there is a change in ratio. As of April 2023, Bank Syariah Indonesia KCP Tanah Sareal has 113 planned savings product customers. Keywords : savings plan, akad mudharabah muthlaqah